HUBUNGAN KEKERABATAN AKSESI PISANG KEPOK (Musa paradisiaca Formatypica) DI KABUPATEN MUNA BERDASARKAN KARAKTER MORFOLOGI DAN PENANDA RAPD - Wijayanto, Teguh; Boer, Dirvamena; Ente, La (Jurnal Agroteknos, 2013)
Twenty-four accessions that belong to four groups of kepok banana in Muna Regency have   been   analyzed   for   their   genetic   diversity   based   on   morphological   characters (qualitative and quantitative characters), and a few accessions based on RAPD markers. This study aimed to determine the genetic diversity and phylogenetic relationship of accessions of kepok bananas based on 52 qualitative and 12 quantitative morphological characteristics and DNA characteristics.   Results of clustering analysis showed the euclidian values ranged between 0.50 to 1.00 for the qualitative data, 0.01 to 0.50 for quantitative data, and 0.83 to 0.88  for  DNA  profile  data.  Combined  qualitative  and  quantitative  data  had  similarity coefficient ranged from 0.00 to 2.50.  Dendogram of each character produced 2 main groups. The main group 1  formed subgroups. Although the qualitative and quantitative characters resulted in different accession   groupings, the combined data analysis of quantitative and qualitative  data  showed  that kepok  banana  in  Muna  regency  was  classified into    4  sub groups namely banana Manuru, Bugisi, Jiwaka and Manuru Lakabu. Keywords:   cluster   analysis,   kepok   banana,   qualitative   and   quantitative   characters, morphology, RAPD markers.